Rancang Bangun Sistem Informasi Administrasi Sirkulasi Majalah dan Koran pada PT. Prima Nadia Gravia - Raharjo, Ahmad Rizal Syafikri; Nurcahyawati, Vivine; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Prima Nadia Gravia is a company engaged in the field of services that place on the Jl. Cipta Menanggal VI No. 7 Surabaya, the company serves advertising services and information services in the form of magazines and newspapers published within a certain time and spread throughout Indonesia, especially in the city of Jakarta and Surabaya. In terms of distribution of newspapers and magazines, PT. Prima Nadia Gravia uses the Circulation section. In the current Circulation section, the business process used is still very manual, all the recordings still use Microsoft Word, Microsoft Excel and archived paper files and still no record of payment and receivable customers causing harm to the company.The solution is to conduct a research and design of Information System that can help the circulation to control how the circulation activities that run better than ever. Development method used is System Development Life Cycle Waterfall Method.The expected result is that it can help corporate secretary to control circulation activity and give report related to payment and receivable of customers so that editor in chief can know earnings report from circulation activity.